Effects of the Junior Master Gardener’s (JMG) Curriculum on Guatemalan Students’ Knowledge Gain and Attitude toward Science - Anna Glenn; Gary Wingenbach (Journal of International Agricultural and Extension Education, 2015)
We examined the impact of selected Junior Master Gardeners (JMG) lessons on students’ science knowledge gain and attitudes toward science. Sixth-grade students (N = 84) and teachers (N = 11) from two rural schools in Guatemala participated in six weeks of JMG lessons. Students completed pre- and post-science knowledge tests, and pre- and post-science attitude surveys. Teachers also completed surveys to evaluate their perceptions of JMG lessons and their perceived impacts those lessons had on students’ science learning and attitudes. Results showed students’ science knowledge significantly increased as a result of their participation in JMG lessons. No change in attitude toward science was observed in the student data; however, data from teachers’ surveys indicated teachers perceived JMG lessons were important in stimulating students’ desires to learn science and in increasing students’ interests in science. The lack of significant change in students’ science attitudes may be attributed to low internal reliability scores for the scale; many previous studies conducted in the U.S. indicated participation in 4-H, JMG, and other agricultural education activities facilitated changes in attitudes toward science. Overall, this study suggests there is great potential for using JMG programs in developing countries. Because of its impact on science education, JMG programs should be accepted as viable tools for international development projects focused on more educated and capable youth populations. Both science knowledge and attitudes toward science are closely associated with economic prosperity and successful livelihoods.
Keywords: Science Education; Junior Master Gardeners; Development Projects